(untitled) (Plant Tissue Culture and Biotechnology, 2021)
In general, antimicrobial agents are often used in micropropagation techniques to obtain contaminant free clones. The objective of the present study was to evaluate the effects of bavistin and cefotaxime on producing contaminant free plants of Ruellia tuberosa cultured on MS supplemented with phytohormones. Field grown nodal explants of Ruellia tuberosa was used to regenerate entire plants via direct organogenesis. Among the decontaminants tested, the fungicide bavistin along with higher concentration of BAP (2.0 mg/l) and lower concentration of NAA (1.0 mg/l) was the most effective in regeneration and producing contaminant free shoots from cultured explants. This fungicide at 300 mg/l minimised fungal contamination with survival rate of 54%. While the addition of decontaminant cefotaxime at low concentration (200 mg/l) along with same concentration of BAP and NAA stimulated the bud formation and controlled the bacterial contamination. However, its increasing concentration adversely affected the survival rate of Ruellia tuberosa. These findings clearly showed that low concentrations of bavistin and cefotaxime were not only non-toxic but also facilitated bud regeneration. The results achieved showed the decisive role not only of the use of successful fungicides and antibiotics, but also of their sufficient doses were very important in reducing contamination and helping multiple shoot proliferation. Plant Tissue Cult. & Biotech. 31(1): 1-12, 2021 (June)